Pengembangan LKPD Berbasis Android dengan Pendekatan STEM untuk Meningkatkan Kemampuan Berpikir Kritis - Syir' Anatut Taqiyyah; Bambang Subali Subali; Suharto Linuwih; Ellianawati; Siswanto; Mohammad Mubarrak bin Mohd Yusof (Postgraduate, University of Mataram, 2023)
Critical thinking is a basic skill needed in the 21st century. This research aims to determine the feasibility, effectiveness, influence and response of Android-assisted LKPD students using a STEM approach to improve students' critical thinking skills. This type of research is R&D with the ADDIE type. This research sample used a purposive sampling technique in small-scale and large-scale trials at SMP Negeri 2 Demak. The aspects of critical thinking ability studied are aspects of explaining, analyzing, evaluating, concluding, interpreting, synthesizing, inferring. The research results show that, 1) Android-assisted LKPD with a STEM approach is suitable for use in learning science and optical instrument material; 2) Android-assisted LKPD with a STEM approach is able to improve critical thinking skills with an N-Gain value of 70.82% in the high category; 3) Android-assisted LKPD with a STEM approach has an effect on critical thinking skills with a tcount of 24.484; 4) Student responses to Android-assisted LKPD with a STEM approach obtained a percentage of 85% with the strongly agree category. Based on the results of this research, it can be concluded that Android-assisted LKPD with a STEM approach is suitable for improving critical thinking skills.